STATE AND DYNAMICS OF LAND RELATIONS IN BULGARIA - A REVIEW - Teodora STOEVA; Violeta DIRIMANOVA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The institutional environment in Bulgarian agricultural sector is a complex system of relationships, dynamically changing under the influence of national and sectoral legislation. Over the last 16 years, was characterized as a difficult period for agriculture and land relations in Bulgaria – because of insufficient legislation the Ownership and Use of Agricultural Land Act about 34 changes have been made to the Act, which are directed in the interest of agricultural users. The changes made concern the concluded contracts for the use and lease of the agricultural land. The dynamics and future changes in land relations are inextricably linked to changes in European and national policy. Receiving European subsidies and financial support to the income of Bulgarian farmers deforms the economic environment in our country. The European subsidies are a key motive and priority for farmers. The purpose of this paper is to describe the state in Bulgarian agricultural sector which is characterized by intensity and dynamics, more complexity and instability. The value of the gross agricultural output had declined during the last years. This research work is based on the following methodological approaches: complex, structural and comparative. The theoretical framework of this article provides a summary overview of the main institutional changes in the agricultural policy and the structure of land relations in Bulgaria. For the purposes of the research different information sources have been used - scientific journals, as well as the author's own research.